Glycerol-preserved corneal tissue in emergency corneal transplantation: An alternative for fresh corneal tissue in COVID-19 crisis - Neeti Gupta (Indian Journal of Ophthalmology, 2020)
Purpose: Due to the COVID-19 pandemic, most of the eye banks have limited/stopped corneal collection, as this is a highly contagious disease. This has led to shortage of donor corneas worldwide. Glycerol preservation of tissue remains a viable option in this scenario. The objective is to compare fresh corneal tissue (FCT) with glycerol-preserved cornea (GPC) in emergency corneal transplantation. Methods: This was a retrospective cohort study conducted in a tertiary care centre of Uttarakhand. Medical records of the patients who underwent therapeutic penetrating keratoplasty (TPK) were reviewed. FCT group included patients who underwent TPK with fresh corneal tissue and GPC group included patients who underwent TPK with glycerol preserved cornea. The indications and outcomes of TPK in the terms of therapeutic success were analysed and compared between both the groups. Results: A total of 94 eyes of 91 patients underwent TPK from October 2011 to August 2017. FCT group included 60 eyes of 57 patients and GPC group included 34 eyes of 34 patients. The primary indication of TPK was infectious keratitis in both the groups (FCT-81.6%; GPC - 91.2%) There was no significant difference in the therapeutic success in both the groups (P = 0.741, Odds ratio- 1.59 with 95% CI- 0.39-6.44). Complications included glaucoma (FCT-21.7%; GPC- 35.2%) graft infection (FCT- 18.33% GPC- 2.9%); graft rejection (FCT-11.66%, GPC- 0%); and graft failure (FCT-88.33%, GPC-100%). Conclusion: The GPC is comparable to FCTs in therapeutic transplant and can be a useful interim procedure in saving the eyes in cases of infective keratitis in the time of crisis.